PERAN KOMISI PERLINDUNGAN ANAK INDONESIA (KPAI) DALAM PERLINDUNGAN KORBAN KEKERASAN ANAK (Martabat: Jurnal Perempuan dan Anak, 2018)
Implementation Protection of children is an obligation that must be upheld and carried out in accordance with the Law of the Republic of Indonesia concerning child protection. This Act was made with the aim of protecting children from crime and acts of violence committed by people who do not have a sense of humanity, as well as an effort to reduce various acts of violence experienced by children in all aspects. This research is descriptive qualitative research with deductive and comparative analysis. The results of this study have a role in the effort to protect children and protect every child whether as a child or as a victim of violence. The thing that must be known is that the rights of a child, both women and men are equally protected in other words, this institution provides an opportunity for every child to make changes (rehabilitation), while in carrying out the court system and peace between the victims and KPAI's institutional actors do not act immediately because of prior confirmation or asymmetry.   Keywords: KPAI, qualitative research, violence of children